PENGARUH KUALITAS PELAYANAN SPBU TERHADAP KEPUASAN KONSUMEN DI KABUPATEN BURU (STUDI PADA SPBU LALA) : (The Effect of Quality of SPBU Service to Customer Satisfaction in Buru Regency) - Hamdani Kubangun; Kalidupa, Muhamad (Uniqbu Journal of Exact Sciences, 2020)
In Indonesia, one of the companies that produces and supplies fuel is PT Pertamina (Persero). Pertamina continues to develop new service standards to ensure consumers get the best service. SPBU (Public Fuel Filling Station) is a private party working together as a means to distribute products produced by Pertamina. This study aims to determine the effect of service quality on customer satisfaction at local gas stations and to determine the most dominant factor influencing customer satisfaction at local gas stations, using 68 respondents of this study using linear regression methods and t test. Linear regression with equation Y = 3.263 + 0.192X. Based on the results of calculations from the statistical t test between service quality variables on customer satisfaction, obtained t value of 1.787 and t table value of 2.00 This means t arithmetic <t table (1,787 <2.00), meaning that there is no influence on service quality to customer satisfaction, which means that Ho is accepted and Ha is rejected. so, in this case it can be concluded that there is an influence of service quality on customer satisfaction with a significance value of 0.078> 0.05, then Ho is accepted and Ha is rejected, it means there is no influence of Variable X (quality of service) on customer satisfaction (variable Y) so, in this case it can be concluded that there is no significant effect of service quality on consumer satisfaction at the Lala gas station.